X-ray structural and spectroscopic investigation of 1-piperidine-2,4-dinitrobenzene - Ellena, Javier Alcides (1995)
The crystal structure of the title compound (C11H13N3O4) has been determined by single-crystal X-ray diffraction. The compound is monoclinic, space group P21/n, witha=9.968(2),b=9.156(2),c=13.249(2)A, β=102.05(2)°, andDx=1.563 gcm−3 forZ=4. The aromatic ring shows a slight boat deformation. Theo- andp-NO2 groups are twisted out of the plane of the phenyl ring by 39.0(2)° and 4.4(1)°, respectively. The piperidine ring exhibits a slightly deformed chair conformation. Short C−H...O intermolecular contacts stabilize the three dimensional structure. UV and NMR data indicate that the molecule in solution presents a conformation similar to that of the the solid state.